Hubungan Status Ibu Bekerja, Pola Asuh Makan, Pemberian ASI Eksklusif dengan Kejadian Picky Eater pada Anak Usia Prasekolah - Pangestuti, Frizma Yuanita; Prameswari, Galuh Nita (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2021)
ABSTRACT Background: Malnutrition is very commond in preschool children, one of which is influenced by picky eating behavior. The prevalence of malnutrition toddlers in Central Java reached 13.68% and in Semarang City in 2018 the prevalence increased from 2017 to 2.43%. The results of a preliminary study at the TK IT Al Kamilah as many as 60% of children experience picky eaters. The research aim is to identify the relation between the status of working mothers, parental feeding style, exclusive breastfeeding with the incidence of picky eater in preschool children. Methods: The research design is cross sectional with sample of 89 respondents which stratified random method and data measured using a CEBQ and PFSQ questionnaires. The independent variables studied were the status of working mothers, parental feeding style, exclusive breastfeeding and the dependent variable studied was the incidence of picky eater. Data analysis was analyzed with chi square test, fisher exact test and kolmogorov smirnov test (α = 0.05). Results: there is relationship between the status of working mothers (p-value=0,018) with the incidence of picky eater, parental feeding style (p-value=0.984) and exclusive breastfeeding (p-value=0.137) had no relationship with the incidence of picky eater. Conclusion: Mothers need to pay attention to food intake during pregnancy and breastfeeding. Keywords: parental feeding, picky eater, preschool children ABSTRAK Latar Belakang: Anak usia prasekolah rentan mengalami gizi kurang yang salah satunya dipengaruhi oleh perilaku picky eating. Prevalensi balita gizi kurang di Jawa Tengah mencapai 13,68% sedangkan di Kota Semarang tahun 2018 prevalensinya meningkat dari tahun 2017 menjadi 2,43%. Hasil studi pendahuluan di TK IT Al Kamilah sebanyak 60% anak mengalami picky eater. Tujuan penelitian ini untuk mengetahui hubungan status ibu bekerja, pola asuh makan, pemberian ASI eksklusif dengan kejadian picky eater pada anak usia prasekolah. Metode: Penelitian ini menggunakan rancangan cross sectional, dengan jumlah sampel sebanyak 89 responden yang ditentukan dengan menggunakan metode stratified random sampling dan data diukur menggunakan kuesioner CEBQ dan PFSQ. Variabel bebas yang diteliti adalah status ibu bekerja, pola asuh makan, pemberian ASI eksklusif dan variabel terikat yang diteliti adalah kejadian picky eater. Analisis data dilakukan dengan uji chi square dan uji kolmogorov smirnov (α=0,05) Hasil: Terdapat hubungan antara variabel status ibu bekerja dengan kejadian picky eater (p-value=0,044), variabel pola asuh makan (p-value=0,997) dan pemberian ASI eksklusif (p-value=0,331) tidak ada hubungan dengan kejadian picky eater. Kesimpulan: ibu perlu memperhatikan preferensi makan selama masa kehamilan dan menyusui. Kata kunci: anak prasekolah, picky eater, pola asuh makan